(untitled) (Journal of Universal Science Research, 2025)
The rapid expansion of social media platforms has significantly changed how learners interact with the English language. For English as a Foreign Language (EFL) learners, social media provides authentic input, opportunities for interaction, and exposure to diverse vocabulary in real-life contexts. This paper investigates the impact of social media on vocabulary acquisition, examining both its positive contributions and potential drawbacks. The study is based on a mixed-methods approach, combining a survey of 120 EFL students with classroom observations.